Urgensi Sertifikat Laik Fungsi Bangunan Gedung Dengan Objek Izin Apotek - Tri Mulyani; Alief Azza Baharuddin; Ahmad Faiz Akbar (Universitas Semarang, 2023)
The purpose of this study was to analyze the impact of implementing the policy of issuing Certificates of Proper Function (SLF) for Buildings in relation to pharmacy licenses in Kendal Regency and their solutions. The urgency of this research is considering that so far there have been many complaints from the public regarding the high cost of SLF, while SLF is proof that the building can be relied upon and utilized. The approach method in this research is sociological juridical. The results of the study show that the impact of the implementation of the building SLF issuance policy in relation to pharmacy licenses in Kendal Regency was carried out by a team of technical reviewers of building feasibility tests originating from the private sector at different rates according to their competence and experience resulting in expensive costs. The solution that has been carried out by the agency so far is to coordinate with local governments and consultants to further reduce costs. Then simplify the SIA application requirements by requiring the completion of the SLF for a period of 1 year accompanied by a statement of commitment. But in fact a solution is needed in the form of a political elite approach to state institutions needed to equalize people's perspectives with regard to the procurement of CPNS, the format of a building adequacy consultant and the revision of the Job Creation Law as well as the establishment of a Ministerial Regulation for Administrative Reform and Bureaucratic Reform concerning the Procurement of CPNS PUPR. Tujuan penelitian ini adalah untuk menganalisis dan mengetahui implikasi pelaksanaan kebijakan penerbitan Sertifikat Laik Fungsi (SLF) Bangunan Gedung dalam kaitannya dengan izin apotek di Kabupaten Kendal beserta solusinya. Adapun urgensi penelitian ini mengingat bahwa selama ini banyak dikeluhkan masyarakat terkait mahalnya biaya SLF, sedangkan SLF merupakan bukti bahwa bangunan dapat diandalkan dan dimanfaatkan. Metode pendekatan dalam penelitian ini adalah yuridis sosiologis. Hasil penelitian menunjukkan bahwa dampak pelaksanaan kebijakan penerbitan SLF bangunan gedung kaitannya dengan izin apotek di Kabupaten Kendal dilakukan tim pengkaji teknis uji kelaikan bangunan gedung berasal dari swasta dengan tarif yang berbeda-beda disesuaikan dengan kompetensi dan pengalamannya sehingga mengakibatkan biaya menjadi mahal. Solusi yang dilakukan oleh dinas selama ini adalah berkoordinasi dengan pemerintah daerah dan konsultan untuk lebih menekan biaya. Kemudian menyederhanakan persyaratan permohonan SIA dengan mewajibkan melengkapi SLF selama kurun waktu 1 tahun disertai pernyataan komitmen. Namun sesungguhnya diperlukan solusi berupa pendekatan elite politik terhadap kelembagaan negara diperlukan guna penyamaan prespektif masyarakat berkaitan dengan pengadaan CPNS formatur konsultan kelaikan bangunan gedung dan revisi UU Cipta Kerja serta pembentukan Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi tentang Pengadaan CPNS Formatur Konsultan Kelaikan Bangunan Gedung di Kementerian PUPR.